Investigating Radical Deaths and the Cultures That Practiced Them: New AHRC Funded Research at the Institute of Archaeology. Issue 1 (17th January 2020) - Hassett, Brenna R.; Wengrow, David; Sağlamtimur, Haluk
Abstract : A new Arts and Humanities Research Council (AHRC) funded project brings together multiple strands of investigation to probe the relationship between ritual, violence, and early state formation. David Wengrow and Brenna Hassett will coordinate an international team combining biomolecular analysis (stable isotopes, ancient DNA), bioarchaeology, and archaeology to examine a remarkable set of Early Bronze Age funerary deposits (c. 3100–2800 BC), excavated at the multi-period site of Başur Höyük, in South-eastern Turkey. They include evidence of extraordinary wealth combined with radically new cultural practices, such as mass death pits and burials of retainers or other human victims. Such findings add to a growing body of archaeological data from the Middle East, which is now prompting researchers to rethink key aspects of social and political change at the start of the Bronze Age.